Graphics recognition : current trends and evolutions : 12th IAPR International Workshop, GREC 2017, Kyoto, Japan, November 9-10, 2017, Revised selected papers /: current trends and evolutions : 12th IAPR International Workshop, GREC 2017, Kyoto, Japan, November 9-10, 2017, Revised selected papers. (2018) - Unknown
No abstract available